Optimalisasi sistem kelas virtual berbasis google classroom dan hipnoterapi - Imma Rachayu; Diah Selviani (Journal Of Dehasen Educational Review, 2020)
The purpose of this study was to optimize the virtual classroom system based on google classroom and hypnotherapy during the Covid-19 pandemic. The research method uses qualitative research, namely literature, interviews, the making process, implementation and evaluation. The results showed that of the 37 students there were 27 students who worked on assignments and exam questions on time based on the agreed time before the exam started with a percentage of 73%. While 10 people have not been able to be on time in doing the assignments and exam questions that have been given with a percentage of 27%. The cause based on the interview were network limitations. In this study it can be concluded that the optimization of the virtual class system is able to provide benefits in the use of google classrooms for lecturers and students during the Covid-19 pandemic by providing assignments, assessment schemes, active communication in discussing material, time efficiency in the learning process. In line with the learning process students are given suggestions in their subconscious mind to stay focused and concentrate on the lecture material and be able to manage their positive thought patterns and actions in accordance with the expectations of lecturers and parents.